2000
DOI: 10.1021/jm000033p
|View full text |Cite
|
Sign up to set email alerts
|

Benzothiadiazine Dioxide Dibenzyl Derivatives as Potent Human Cytomegalovirus Inhibitors:  Synthesis and Comparative Molecular Field Analysis

Abstract: The benzothiadiazine dioxide (BTD) derivatives are potent nonnucleoside human cytomegalovirus (HCMV) inhibitors. As part of our comprehensive structure−activity relationship study of these compounds, we have now synthesized N,N- and N,O-dibenzyl derivatives with different para-substituents (alkyl, phenyl, electron-donating, electron-withdrawing) in the phenyl ring of the benzyl moieties. The antiviral activity against HCMV (AD-169 strain) was also experimentally measured showing IC50 values between 2.5 and 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 20 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…Synthesis of N-Aminosulfonyl-o-carboranylmethyl-1,2,3,4-tetrahydroisoquinolines. As an extension of these studies, the reaction of the aminosulfonyl functionalized arylethylamine (13) with o-carboranylacetaldehyde diethyl acetal (4, 5) was investigated in order to evaluate the effect of placing a sulfonyl group on the amine functionality. It has been noted that the sulfamide moiety is widely represented in many natural products and plays an important role in biological activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of N-Aminosulfonyl-o-carboranylmethyl-1,2,3,4-tetrahydroisoquinolines. As an extension of these studies, the reaction of the aminosulfonyl functionalized arylethylamine (13) with o-carboranylacetaldehyde diethyl acetal (4, 5) was investigated in order to evaluate the effect of placing a sulfonyl group on the amine functionality. It has been noted that the sulfamide moiety is widely represented in many natural products and plays an important role in biological activities.…”
Section: Resultsmentioning
confidence: 99%
“…It has been noted that the sulfamide moiety is widely represented in many natural products and plays an important role in biological activities. 13 The synthesis of the aminosulfonyl tetrahydroisoquinoline skeleton was performed based on the α-sulfamidoalkylation procedure 14 previously reported by us (Scheme 2). The requisite aminosulfonyl functionalized arylamines (13) could be conveniently prepared by aminosulfonylation of the nitrogen atom of 14-17 according to established synthetic protocols.…”
Section: Resultsmentioning
confidence: 99%
“…The model suggested that the steric component is a predominant factor in the antiviral activity of these analogs with electrostatic factors playing a smaller yet significant role [16]. Subsequently, novel series of non-nucleoside anti-HCMV inhibitors were synthesized and showed specific anti-HCMV effects.…”
Section: Newly Designed Btd Derivatives Based On Comfa Modelmentioning
confidence: 99%
“…I, II, R 1 = H (a), Me (b); III, R 1 = Me, R 2 = H, R 3 = 1,3-thiazol-2-yl (a); R 1 = R 2 = H: R 3 = 4-FC 6 Compounds containing a fragment N-SO 2 -N exhibit antiviral action [1], inhibit phosphodiesterase [2], are antagonists of dopamine D2 [3] and leucotriene [4].…”
mentioning
confidence: 99%